Political Economy Analysis - How to note - DFID (DFID, 2009)
Political economy analysis is a powerful tool for improving the effect iveness of aid. Bridging the traditional concerns of politics and econ omics, it focuses on how power and resources are distributed and conte sted in different contexts, and the implications for development outco mes. It gets beneath the formal structures to reveal the underlying in terests, incentives and institutions that enable or frustrate change. Such insights are important if we are to advance challenging agendas a round governance, economic growth and service delivery, which experien ce has shown do not lend themselves to technical solutions alone. Poli tical economy analysis is not a magic bullet for the resolution of int ractable development problems. However, it can support more effective and politically feasible development strategies, as well as inform mor e realistic expectations of what can be achieved, and the risks involv ed. It can also contribute to better results by identifying where the main opportunities and barriers for policy reform exist and how donors can use their programming and influencing tools to promote positive c hange. This understanding is particularly relevant in fragile and conf lict-affected environments where the challenge of building peaceful st ates and societies is fundamentally political. There are an increasing number of political economy tools available to development agencies f or a range of analytical and operational purposes. This note brings to gether this material with a view to explaining the relevance and uses of political economy analysis. It is intended to be used by a wide ran ge of DFID programme managers and advisers, as well as staff in other HMG departments and partner organisations. The main questions it addre sses are: ?? what is political economy analysis? ?? how and why does p olitical economy analysis add value to DFID work? ?? what approaches a nd tools are available? ?? how should the analysis be prepared, undert aken and applied to DFID’s work? ?? how should we work with other deve lopment partners and across HMG on analysis? Key messages include: • P olitical economy analysis is central to the formulation of sound count ry plans and sector programmes, and can play a key role in risk mitiga tion and ensuring that donors avoid harmful practices. • Political eco nomy analysis can help to improve development effectiveness by identif ying how and where donors should focus efforts to promote positive cha nge. • There are a growing number of operationally relevant tools whic h can be used to inform development strategies at the country or secto r level, or in relation to particular development problems. • Several DFID country offices have used political economy analysis to improve t he quality and impact of aid. This experience provides valuable lesson s that should be considered when commissioning and undertaking politic al economy analysis. • Where possible, analysis should be conducted on an ongoing basis with key partners in HMG and the wider development c ommunity to encourage shared understanding and joint action.